Identification Of Nitrogen Fixing Microsymbionts From Mucuna Bracteata Nodules - Shaffie, Salwani (2011)
Mucuna bracteata is a new leguminous cover plant which forms nodules and establises a nitrogen-fixing symbiosis. However, there is little information available on the N2-fixer of M. bracteata. Rhizobia are used to be recognized for all the bacteria that are able to produce nodule and fix N2 in legume’s root and collectively a member of the Rhizobiaceae in α-class of proteobacteria. There have been an increasing number of bacteria that can nodulate and fix N2 in legume which are not belong to the original genus Rhizobium in Rhizobiaceae family and traditional rhizobial phylogenetic lineages.